2021
DOI: 10.3390/life11030235
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbial Composition and Predicted Functions Are Not Associated with Feather Pecking and Antagonistic Behavior in Laying Hens

Abstract: Background: Feather pecking is a well-known problem in layer flocks that causes animal welfare restrictions and contributes to economic losses. Birds’ gut microbiota has been linked to feather pecking. This study aims to characterize the microbial communities of two laying hen lines divergently selected for high (HFP) and low (LFP) feather pecking and investigates if the microbiota is associated with feather pecking or agonistic behavior. Methods: Besides phenotyping for the behavioral traits, microbial commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…In particular, there is an interest in how ingestion of these supplements in childhood or early-life can shape behaviour. The administration of a single Lactobacillus rhamnosus strain successfully prevented severe feather pecking (SFP) in adult laying hens 73 , possibly by restoring the lower abundance of Lactobacillus reported in SFP birds 50 , 51 , 71 . In the present study, we evaluate the ability of the same L. rhamnosus strain to act as a preventative measure against SFP when administered in early-life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, there is an interest in how ingestion of these supplements in childhood or early-life can shape behaviour. The administration of a single Lactobacillus rhamnosus strain successfully prevented severe feather pecking (SFP) in adult laying hens 73 , possibly by restoring the lower abundance of Lactobacillus reported in SFP birds 50 , 51 , 71 . In the present study, we evaluate the ability of the same L. rhamnosus strain to act as a preventative measure against SFP when administered in early-life.…”
Section: Discussionmentioning
confidence: 99%
“…The Lactobacillus genus is significantly underrepresented in the cecal droppings of feather peckers 50 , 51 , 71 . Furthermore, L. rhamnosus has been demonstrated to attenuate behavioural deficits induced by chronic social stress in mice 72 .…”
Section: Introductionmentioning
confidence: 99%
“…Microbiota populations, their diversity, and composition varied in hens with different diet compositions (Borrelli et al, 2017;Zhou et al, 2021). There is also some evidence that microbiota composition can vary among groups of hens selected for behavioral differences in feather pecking (van der Eijk et al, 2019), although other studies have not found significant differences (Borda-Molina et al, 2021). Housing environments can affect microbial composition with differences found between broiler chickens that had fresh or reused litter on the floor (Wang et al, 2016), or different types of litter substrates (Torok et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although Borda-Molina et al did not find any relations between microbiota and feather pecking [72], there is growing evidence that gut microbiota influence hens behaviour and physiology [73,74]. However, whether microbiota can influence the development of feather pecking is not fully demonstrated [74,75].…”
Section: Main Causes Of Damaging Behaviour and Control Strategiesmentioning
confidence: 96%